PENGARUH KOMPENSASI TERHADAP KOMITMEN KERJA GURU HONOR DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING (Studi Kasus pada Guru Honor SMP di Kecamatan Koto X1 Tarusan Kabupaten Pesisir Selatan) - Novita Sari, Nia; Wahyuni, M.Pd, Sri; S.Pd M.E, Jolianis, (Pendidikan Ekonomi, 2014)
ABSTRACTThis research was motivated by the lack of commitment of teachers working in the district junior honors Tarusan Koto XI. This is due to the lack of compensation received and the low salaries of the teachers job satisfaction This study aims to determine whether there is a compensating effect on the commitment of teachers working in the district junior honors Koto XI Tarusan with job satisfaction as an Intervening variable.Type of research is causative. The population in this studi were junior high teacher salaries in the District XI Tarusan Koto. Sample in this studi were all teachers in the district junior honors Koto XI Tarusan totaling 88 people. The instrument used was a questionnare. To determine the effect of Compensation for Occupational Commitment to Honor Teacher Job Satisfaction as an intervening variable used technique t test.Based on the results of the analysis showed that : 1. Compensation positive effect on the commitment of teachers working in the district junior honors Tarusan Koto XI 2. Compensation positive effect on job satisfactionÂ  of teachers in the district junior honors Tarusan Koto XI, and 3. Positive effect on job satisfaction the commitment of teachers working in the district junior honors Koto Tarusan XI 4. Compensation effect the Work Commitment to Honor Teacher Job Satisfaction as an intervening variable. In order to increase the salaries of teachers to work commitmen junior high school in the district koto XI Tarusan southem coastal district welfare of teachers salaries should be considered through an increase in compensation. In addition, to improve job satisfaction can be done by improving the relationship between superiors and teachers as praise for the work.Â